2004
DOI: 10.1136/bmj.38210.827917.7c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adenotonsillectomy in children with mild symptoms of throat infections or adenotonsillar hypertrophy: open, randomised controlled trial

Abstract: Adenotonsillectomy has no major clinical benefits over watchful waiting in children with mild symptoms of throat infections or adenotonsillar hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
133
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 25 publications
1
133
0
5
Order By: Relevance
“…However, children younger than 6 years of age may also suffer from recurrent episodes of tonsillitis and are therefore candidates for tonsillectomy too. This statement is supported by the studies of Paradise [1 ]who included children 3-15 years of age or van Staaij [2] including children aged 2-8 years. Indication for surgery should rely on the grade, and how seriously the quality of life in that particular individual is impaired rather than counting episodes of tonsillitis or years.…”
mentioning
confidence: 58%
“…However, children younger than 6 years of age may also suffer from recurrent episodes of tonsillitis and are therefore candidates for tonsillectomy too. This statement is supported by the studies of Paradise [1 ]who included children 3-15 years of age or van Staaij [2] including children aged 2-8 years. Indication for surgery should rely on the grade, and how seriously the quality of life in that particular individual is impaired rather than counting episodes of tonsillitis or years.…”
mentioning
confidence: 58%
“…Randomized trials comparing surgical treatment versus medical treatment published since 1966 were selected. They found 1 adult study with 70 patients [40] and 4 pediatric studies totalizing 719 children [41,42,43]. The studies were so heterogeneous that a meta-analysis could not be performed.…”
Section: Recurrent Tonsillitismentioning
confidence: 99%
“…In an open randomized controlled trial, van Staaij et al [43] included 300 children aged 2-8 years requiring TA. The study was conducted in 21 centers.…”
Section: Recurrent Tonsillitismentioning
confidence: 99%
“…A recent Dutch randomised controlled trial of adenotonsillectomy versus watchful waiting reported no differences between treatment arms for children with mild symptoms and only a small difference of less than one episode of fever a year between treatment arms for children with moderate symptoms. 27 The Scottish National Tonsillectomy Audit 14 showed high levels of patient satisfaction and that 80% of subjects did not consult a doctor in the subsequent 12 months. However, over the past 30 years a number of controlled studies with longer follow-up indicate marginal and diminishing levels of clinical benefit over a period of nonintervention.…”
Section: 12mentioning
confidence: 99%
“…Another relative [18][19][20][21][22][23][24][25][26] A friend [27][28][29][30][31][32][33][34][35] A child minder [36][37][38][39][40][41][42][43][44] A nanny [45][46][47][48][49][50][51][52][53] Other (please write in who) …”
mentioning
confidence: 99%